Seedbanks in cerrado sensu stricto under burning and cultivation system - Ikeda, Fernanda Satie; Mitja, Danielle; Vilela, Lourival; Silva, José Carlos Sousa (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to evaluate the burning and cultivation effects on soil seedbanks originally under cerrado vegetation. Two areas under cerrado sensu stricto were sampled, one burned and the other one not burned, as well as areas under tilled crop and pasture. There was no reduction on seedbank, although lower number of species and families and diversity index (Shannon and Simpson) with burning were observed. There was also greater importance value index (IVI) and number of native species, in the non burned area, and of weeds in the burned one. It was observed that the crop area had higher seed density than the pasture and cerrado areas. The species with the highest IVI in the areas were those considered as weeds and forages. The crop area presented lower IVI of native species than the pasture and cerrado areas; besides, it presented diversity indexes (Shannon and Simpson) and native species percentage lower than pasture and cerrado. The cultivation with crop cause higher disturbance in the areas than burning.